RELATIONSHIP BETWEEN SELF-DIRECTED LEARNING, MOTIVATION TO LEARN TOWARD LEARNING ORGANIZATION AMONG LECTURERS AT A SELECTED PUBLIC UNIVERSITY IN MALAYSIA - Kamarruddin, Nur Farhanah; Zainal Abiddin, Norhasni; Idris, Khairuddin (International Journal of Education, 2014)
The purpose of this research is to examine the relationship between self-directed learning, motivation to learn, and learning organization at one public university in Malaysia. Ninety two academic staff were selected through stratified random sampling by post of Professor, Associate Professor, Senior Lecturer, and Lecturer. Three research objectives frame the research: (1) to determine the level of learning organization, self-directed learning, and motivation to learn among lecturers; (2) to determine the relationship between self-directed learning, motivation to learn, and learning organization among lecturers; and (3) to determine the contribution of self-directed learning and motivation to learn on learning organization among lecturers. Descriptive analysis was used to determine the level of self-directed learning, motivation to learn, and learning organization. Pearson Product Moment Correlation’s test was used to determine the relationship between self-directed learning, motivation to learn, and learning organization. Regression analysis was used to determine the contribution of elements of self-directed learning and motivation to learn on organizational learning. Based on the findings of the study, recommendations and policy implications are discussed and directions for future research are provided.